Pigmentation effects of blue light irradiation on skin and how to protect against them. (20th July 2020) - Campiche, R.; Curpen, S. J.; Lutchmanen‐Kolanthan, V.; Gougeon, S.; Cherel, M.; Laurent, G.; Gempeler, M.; Schuetz, R.
Abstract: Background: Visible light, in particular blue light, has been identified as an additional contributor to cutaneous photoageing. However, clinical studies demonstrating the clear effect of blue light on photoageing are still scarce, and so far, most studies have focused on broad‐spectrum visible light. Although there is evidence for increased skin pigmentation, the underlying mechanisms of photoageing in vivo are still unclear. Furthermore, there is still a need for active ingredients to significantly protect against blue light‐induced hyperpigmentation in vivo . Our study had two aims: to detect visible changes in skin pigmentation following repeated irradiation of the skin with LED‐based blue light and to reduce pigmentation using suitable active ingredients. Method: We conducted a randomized, double‐blind and placebo‐controlled clinical study on 33 female volunteers with skin phototypes III and IV. We used a repetitive blue light (4 × 60 J cm −2, 450 nm) irradiation protocol on the volunteers' inner forearms. Using hyperspectral imaging, we assessed chromophore status. In addition, we took chromameter measurements and photographs to assess visible hyperpigmentation. Results: We measured significant changes in chromophore status ( P  < 0.001 vs baseline), that is of melanin, haemoglobin and oxygen saturation, immediately after blue light irradiation. In addition, we found visible skin colour changes which were expressed by a significant decrease in ITA° values (delta ITA° = −16.89, P  < 0.001 vs baseline for the placebo group) and an increase in a * (delta a * = +3.37, P  < 0.001 vs baseline for the placebo group) 24 h post‐irradiation. Hyperpigmentation and skin reddening were mitigated by both a formulation containing 3% of a microalgal product and a formulation containing 3% niacinamide. Conclusion: Our study sets out an efficient and robust protocol for investigating both blue light‐induced cutaneous alterations, such as changes in skin chromophores, and signs of photoageing, such as hyperpigmentation. Moreover, we have shown evidence that both an extract of the microalga Scenedesmus rubescens and niacinamide (vitamin B3) have the potential to protect against blue light‐induced hyperpigmentation. Abstract : We provide here a method to study blue light induced changes in skin in vivo. We show that an algal extract and niacinamide can mitigate blue light induced visible pigmentation and skin reddening. Resume: Contexte: La lumière visible, en particulier la lumière bleue, a été identifiée comme un facteur supplémentaire du photo‐vieillissement cutané. Cependant, les études cliniques, démontrant l'effet réel de la lumière bleue sur le photo‐vieillissement, sont encore rares et jusqu'à présent, la plupart des études portaient sur l'influence de la lumière visible à large spectre. Bien qu'il y ait des preuves concernant l'effet sur la pigmentation de peau, les mécanismes sous‐jacents du photo‐vieillissement in vivo sont encore peu clairs. De plus, le besoin d'ingrédients actifs protégeant de manière significative en in vivo contre l'hyperpigmentation induite par la lumière bleu est toujours présent. Notre étude a eu deux objectifs: Détecter des changements visibles dans la pigmentation de la peau à la suite d'une irradiation répétée avec de la lumière bleue à base de LED, et réduire la pigmentation à l'aide d'ingrédients actifs adaptés. Méthode: Nous avons mené une étude clinique randomisée, à l'aveugle et controlée avec un placebo sur 33 volontaires féminins de phototypes de peau III et IV. Nous avons défini un protocole d'irradiation répétitif à lumière bleue (4 x 60 J cm‐2, 450 nm) sur les avant‐bras intérieurs des volontaires. En utilisant l'imagerie hyperspectrale nous avons évalué l'état de chromophore. En outre, nous avons pris des mesures de couleur et des photographies pour évaluer l'hyperpigmentation de manière visuelle. Résultats: Nous avons mesuré des changements significatifs dans le statut de chromophore (p<0.001 par rapport au statut initial), par exemple au niveau de la mélanine, de l'hémoglobine et de la saturation en oxygène, immédiatement après l'irradiation à lumière bleue. De plus, nous avons constaté des changements visibles de couleur de la peau qui ont été exprimés par une diminution significative des valeurs ITA° (delta ITA° valeurs = ‐16.89, p<0.001 par rapport au statut initial pour le groupe placebo), et une augmentation de a* (delta a* = +3.37, p <0.001 par rapport au statut initial pour le groupe placebo) 24 heures après l'irradiation. L'hyperpigmentation et les rougeurs de la peau ont été atténués par une formulation contenant 3% d'un extrait d'algue ainsi que par une formulation contenant 3% de niacinamide. Conclusion: Notre étude a établi un protocole efficace et robuste pour étudier à la fois les altérations cutanées induites par la lumière bleue, telles que les changements dans les chromophores de la peau, ainsi que les signes de photo‐vieillissement, tels que l'hyperpigmentation. Enfin, nous avons prouvé qu'un extrait de l'algue Scenedesmus rubescens et la niacinamide (vitamine B3) avaient le potentiel de protéger contre l'hyperpigmentation induite par la lumière bleue.